A mismatch: Why non-tenured teachers are ill-prepared to deal with the perceived job insecurity of students in the humanities. (April 2023) - Crone, Vincent CA
Most of the instructional workforce within the humanities in countries like the United States, United Kingdom, Australia, and The Netherlands comprises non-tenure track appointments. This commentary is a starting point in thinking about what the meaning and consequences are of far-reaching casualization for humanities education. Based on my experience as a supervisor of non-tenured early-career teachers in the humanities and on an international exploration of the position of the so-called precariat, I describe the competing, and perhaps irreconcilable, discourses on the importance of the humanities for society and the labour market which these non-tenured teachers must navigate. These discourses put especially non-tenured academics, who are themselves in a very precarious, in an even more disempowered space that is not only detrimental to these non-tenured teachers but also to the students who must learn to deal with perceived job insecurity.